Hrvati u Sloveniji u potrazi za statusom - Vuković, Tomislav, publicist (Array, 2006)
It is not unknown that besides, naturally, the Slovene language, the Hungarian and Italian languages are in official use in those parts of the Republic of Slovenia with mixed ethnicity. This is because, according to the 2002 census, there are 6243 Hungarians and 2258 Italians living in Slovenia. Why Croatian is not an official, recognised language, even though there are almost ten times more Croatians in Slovenia than Hungarians and Italians combined is also known. Croatians are, namely, not officially recognised as a minority. This does not bother politicians too much. Why make the promised path to the European Union more "difficult" for the sake of 60, 70 thousand Croatians living in Slovenia? After this enumeration of the well-known, perhaps one fact is, at least for most of the public, unknown: A Croatian Catholic mission is active in Maribor, gathering Croatian Catholics in this, the second largest city in Slovenia and its environs